2015
DOI: 10.1158/1078-0432.ccr-14-1837
|View full text |Cite
|
Sign up to set email alerts
|

Genome Analysis of Latin American Cervical Cancer: Frequent Activation of the PIK3CA Pathway

Abstract: Purpose Cervical cancer is one of the most common causes of cancer mortality for women living in poverty, causing over 28,000 deaths annually in Latin America and 266,000 worldwide. To better understand the molecular basis of the disease we ascertained blood and tumor samples from Guatemala and Venezuela and performed genomic characterization. Experimental Design We performed HPV typing and identified somatically mutated genes using exome and ultra-deep targeted sequencing with confirmation in samples from M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
55
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 51 publications
13
55
2
1
Order By: Relevance
“…ACCEPTED MANUSCRIPT 10 Investigators have suggested that alterations in the PI3K pathway may play a role in modulating the oncogenic potential of cervical cells [54,55]. Recently, Zhang and colleagues published a comprehensive review highlighting how HPV's oncogenic proteins E5, E6, E7 enhance PI3K pathway signaling via direct activation of PI3K as well as downstream AKT and rpS6K.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…ACCEPTED MANUSCRIPT 10 Investigators have suggested that alterations in the PI3K pathway may play a role in modulating the oncogenic potential of cervical cells [54,55]. Recently, Zhang and colleagues published a comprehensive review highlighting how HPV's oncogenic proteins E5, E6, E7 enhance PI3K pathway signaling via direct activation of PI3K as well as downstream AKT and rpS6K.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…They identified recurrent mutations in MAPK, and mutations in genes such as HLA-B, EP300, FBXW7, NFE2L2,TP53 and ERBB2 in 79 primary squamous cell carcinomas and that of ELF3 and CBFB in 24 adenocarcinomas [6]. A study from Latin America reported mutations in PIK3CA to be a key player both in squamous and adeno cervical carcinomas [16]. Another study on cervical cancer cases of European origin identified PIK3CA, KRAS and FBXW7 to be the most mutated [17].…”
Section: Discussionmentioning
confidence: 99%
“…Additional cervical cancer specimens were provided according to the ethical approval cited. 20 Two hundred sixty-six cervical cancer specimens from a separate cohort 20 were provided in accordance with the ethical approvals cited. In brief, DNA was extracted from cervical cancer tissues (5-10 mg) and stored in RNAlater using the AllPrep DNA/RNA Micro Kit (Qiagen), as directed by the manufacturer.…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
“…A large cohort of cervical cancer cases was tested by ion torrent NGS genotyping at NCI-FNLCR 20 ; the genotypes detected were not reported previously. Twenty HPV genotypes were detected in this cohort, including all 13 high-risk genotypes (16,18,31,33,35,39,45,51,52,56,58,59, and 68).…”
Section: Comparison Of Hpv Genotyping Of Hnscc and Cervical Cancer Ffmentioning
confidence: 99%